Production of Phytotoxic Metabolites by Botryosphaeriaceae in Naturally Infected and Artificially Inoculated Grapevines - Pierluigi Reveglia; Regina Billones-Baaijens; Jennifer Millera Niem; Marco Masi; Alessio Cimmino; Antonio Evidente; Sandra Savocchia (Plants, 2021)
Grapevine trunk diseases (GTDs) are considered a serious problem to viticulture worldwide. Several GTD fungal pathogens produce phytotoxic metabolites (PMs) that were hypothesized to migrate to the foliage where they cause distinct symptoms. The role of PMs in the expression of Botryosphaeria dieback (BD) symptoms in naturally infected and artificially inoculated wood using molecular and analytical chemistry techniques was investigated. Wood samples from field vines naturally infected with BD and one-year-old vines inoculated with Diplodia seriata, Spencermartinsia viticola and Dothiorella vidmadera were analysed by cultural isolations, quantitative PCR (qPCR) and targeted LC-MS/MS to detect three PMs: (R)-mellein, protocatechuic acid and spencertoxin. (R)-mellein was detected in symptomatic naturally infected wood and vines artificially inoculated with D. seriata but was absent in all non-symptomatic wood. The amount of (R)-mellein detected was correlated with the amount of pathogen DNA detected by qPCR. Protocatechuic acid and spencertoxin were absent in all inoculated wood samples. (R)-mellein may be produced by the pathogen during infection to break down the wood, however it was not translocated into other parts of the vine. The foliar symptoms previously reported in vineyards may be due to a combination of PMs produced and climatic and physiological factors that require further investigation.